Pengaruh Volatilitas Hubungan Politik Bilateral Terhadap Keputusan Investasi Perusahaan Multinasional - Eka Wahyu Kasih; Ngadi Permana; Seger Santoso (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to explore the impact of bilateral political volatility on the investment decisions of multinational corporations (MNCs) through a qualitative literature review approach. The analysis reveals that instability in bilateral political relations significantly influences investment decisions, particularly through regulatory uncertainty, geopolitical risks, and disruptions in stakeholder relationships. Companies with strong political connections are better equipped to manage these risks compared to those without similar networks. Mitigation strategies such as geographical diversification and strategic partnerships are identified as key solutions for addressing geopolitical instability. While providing valuable strategic insights, this study is limited to specific geographical and sectoral contexts. These findings highlight the need for further research with broader geographical and sectoral scopes to support strategic decision-making by multinational corporations in increasingly dynamic geopolitical environments.